Uma herança de direitos abstratos: o discurso integracionista no estatuto do índio (1973) e seus efeitos de sentido - Cabrera, Bruna Cielo (2018)
The present master thesis in Linguistics Studies was developed along with theoretical and methodological framework of Discourse Analysis (DA), which has been developed in Brazil based on Michel Pêcheux’s studies, in order to study the Law No. 6.001 of december 19, 1973. This law, also called The Indian Statute, was sanctioned during the military dictatorship in Brazil during the period known as “anos de chumbo” (Years of Lead), with self-declared purpose of preserving Indians’ culture and promoting their progressive integration in the national communion. Focusing on the processes of production of meaning, the present study was developed through materialistic filiation of DA along with other theoretical notions: ideology, memory, Law discourse, subject of Law, civilian capacity or incapacity, politics and domination of the subject. As a result of this articulation, the present thesis sought to understand which effects of sense derived from integration in discourse that was constituted in the Indian Statute through the guardianship established in this legislation, which determines indigenous deprived from their civil rights or full of their civil capacity when considered integrated or isolated from the national communion. Taking this concern into account, a search was carried out on the national legislations from the period of Brazil’s independence from Portugal until the elaboration of the thesis’ object. In order to trace which echoes reverberate the constitution of an integration discourse in the Statute as a discursive materiality constituted by history, the following were selected for analysis: Law of October 27, 1831; the Brazilian Civil Code of January 1st, 1916; Decree number 5484 of june 27, 1928; Brazilian Constitution of 1934; Brazilian Constitution of 1946 and Brazilian Constitution of 1969. The notion of archive (PÊCHEUX, [1988] 2014) was used as theoretical- methodological procedure for the analysis. The discursive sequences that constitute the present thesis’ corpus of analysis were selected from this archive (ORLANDI, 1984) and were organized according to their relations, sometimes paraphrased, sometimes reiterated. Throughout the theoretical and analytical reflections regarding the object, the discourse was understood as a materialization of state domination and it was designated (GUIMARÃES, 2005) as an integrational discourse of dual functioning. The discourse dual functioning in the Statute and its effects of sense are due to the fact that, even the State working through a protectionist imaginary to integrate indigenous peoples, it alienates them from the concept of unity, since those considered as integrated do not have a level of citizenship. Without a retaliation to the State for what it owes by ligitation (RANCIÈRE, 1996), a course of meanings is composed, which leads to a matter of constitution of the indigenous subject, which is intersect by interdictions of the legal order, which are understood as a process of domination (RANCIÉRE, 1996) that materializes in the language of wood carved by the iron language of the State (GADET; PÊCHEUX, 2010).